2011
DOI: 10.1007/s00203-010-0670-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical properties of the S-layer protein from the wine bacterium Lactobacillus hilgardii B706

Abstract: Different strains of the genus Lactobacillus can be regularly isolated from must and wine samples. By various physiological activities, they can improve or reduce the wine quality. Lactobacillus hilgardii that is known to survive under harsh wine conditions is classified as a spoilage bacterium, e.g. due to the production of histamine. Many lactobacilli form an S-layer as the outermost cell wall component which has been found to facilitate the colonization of special ecological niches. A detailed understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…It could, therefore, be concluded that the S-layer protein consists of two equal-sized domains, and only one of those is sensitive against the protease of S. albidoflavus B 578. A similar result was found in our previous study for the S-layer protein from a Lactobacillus hilgardii strain [22].…”
Section: Degradation Of S-layer Proteins By the Purified Proteasesupporting
confidence: 91%
See 2 more Smart Citations
“…It could, therefore, be concluded that the S-layer protein consists of two equal-sized domains, and only one of those is sensitive against the protease of S. albidoflavus B 578. A similar result was found in our previous study for the S-layer protein from a Lactobacillus hilgardii strain [22].…”
Section: Degradation Of S-layer Proteins By the Purified Proteasesupporting
confidence: 91%
“…Some experimental data give hints that the proteases cleave peptide bonds in the peptidoglycan or the outer membrane of Gram-negative bacteria [41]. Another possible target are S-layer proteins, which comprise the outer cell border of many Archaea and Gram-positive bacteria, including lactic acid bacteria [22] [42] [43]. In this study, we found that the purified protease degrades S-layer proteins from L. brevis B 190, and previously, we demonstrated that the S-layer of Lactobacillus hilgardii B706 was degraded by the culture supernatant of S. albidoflavus B 578 [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial S-layer protein was predicted to have a transmembrane helix and undergo a posttranslational modification by signal peptide excision (45,46). The Avin_16040 protein was also predicted to have a transmembrane helix at the N terminus preceded by an overlapping signal peptide of 20 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…A remarkable characteristic of S-layer proteins is their strong resistance to extreme environmental conditions such as high ionic strength, low pH and high temperature (Claus et al, 2002;Engelhardt & Peters, 1998), suggesting that they contribute to the stabilization and protection of the cells (Claus et al, 2005). S-layer proteins work as molecular sieves and molecule and ion traps, and have in particular the ability to selectively bind heavy metal ions (Dohm et al, 2011;Merroun et al, 2005;Raff, 2002;Sára & Sleytr, 1987).…”
Section: Introductionmentioning
confidence: 99%